2021
DOI: 10.1021/acscatal.1c01949
|View full text |Cite
|
Sign up to set email alerts
|

How Trace Impurities Can Strongly Affect the Hydroconversion of Biobased 5-Hydroxymethylfurfural?

Abstract: Selective conversion of 5-hydroxymethylfurfural (HMF) to liquid fuels is an important step in the valorization of carbohydrates. Although not paid much attention to in the scientific community, we discovered an enormous impact of the HMF purity on the product selectivity during its hydroconversion in the presence of Ru/C. The presence of dimethyl sulfoxide (DMSO) showed the most dramatic effect on the aromatic hydrogenation activity, with almost full selectivity for either 2,5dimethylfuran (DMF) or 2,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
(46 reference statements)
2
31
1
Order By: Relevance
“…Transition metal/acid supports are widely used as heterogeneous catalysts in various tandem reactions including hydrogenation catalysis and acid catalysis in the modern chemical industry. [1][2][3][4] To decrease the carbon footprint and develop a sustainable economy, these catalysts have attracted widespread interest for use in the upgrading of unsaturated biomassderived C 6 furfurals (5-methylfurfural, 5-hydroxymethylfurfural) to valuable chemicals, such as hydrogenative etherification to furan ethers (2-alkoxymethyl-5-methylfuran, 2,5-bisalkoxymethylfuran), [5][6][7] hydrogenative ring-rearrangement to cyclic ketones (3-methylcyclopentanone, 3-hydroxymethylcyclopentanone), [8][9][10][11][12][13] hydrogenative hydrogenolysis to 2,5dimethylfuran and 2,5-dimethyl tetrahydrofuran, [14][15][16] hydrogenative ring-opening to linear ketones (1-hydroxyl-2,5-hexanedione, 2,5-hexanedione). [17][18][19] Among these compounds, 2,5-hexanedione (HD) is an important high-value commodity chemical for performing various upgrades to solvents, polymers, fragrances, and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal/acid supports are widely used as heterogeneous catalysts in various tandem reactions including hydrogenation catalysis and acid catalysis in the modern chemical industry. [1][2][3][4] To decrease the carbon footprint and develop a sustainable economy, these catalysts have attracted widespread interest for use in the upgrading of unsaturated biomassderived C 6 furfurals (5-methylfurfural, 5-hydroxymethylfurfural) to valuable chemicals, such as hydrogenative etherification to furan ethers (2-alkoxymethyl-5-methylfuran, 2,5-bisalkoxymethylfuran), [5][6][7] hydrogenative ring-rearrangement to cyclic ketones (3-methylcyclopentanone, 3-hydroxymethylcyclopentanone), [8][9][10][11][12][13] hydrogenative hydrogenolysis to 2,5dimethylfuran and 2,5-dimethyl tetrahydrofuran, [14][15][16] hydrogenative ring-opening to linear ketones (1-hydroxyl-2,5-hexanedione, 2,5-hexanedione). [17][18][19] Among these compounds, 2,5-hexanedione (HD) is an important high-value commodity chemical for performing various upgrades to solvents, polymers, fragrances, and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting results, for instance, were obtained while optimizing HMF conversion to DMTHF using Ru/C catalyst. [70] A dual catalytic behavior was found during the screening of various high purity HMF feedstocks (> 97 %) from commercial suppliers. The key reaction product was either DMTHF with a yield of > 70 % or DMF with a yield of > 90 %.…”
Section: Feedstock Impuritiesmentioning
confidence: 99%
“…[91] The commercial sample supplied by Sigma Aldrich contained 0.5 wt% of DMSO, which is consistent with a previously discussed report. [70] Authors decided to dope the reaction feed with additional DMSO, while using 15 wt% Ni/SiO 2 catalyst. While no shift in selectivity was discussed, the recent results, similarly as with Ru/C, indicate a rate deactivation effect of DMSO when its concentration increased from 0.5 to 8.5 wt%.…”
Section: Feedstock Impuritiesmentioning
confidence: 99%
“…Turkin et al showed that a sudden and considerable product selectivity shift from DMTHF to 2,5-DMF in the Ru/C-catalyzed hydroconversion of 5-HMF was triggered by the presence of incompletely removed DMSO found in different commercial HMF feedstocks. [81] Therefore, it is highly desired to integrate catalytic steps in which the 5-HMF intermediate generated from raw biomass is directly subjected to the next transformations (oxidation, hydrogenation, oxidative esterification, etc.) to provide valuable products in one-pot fashion.…”
Section: Chemsuschemmentioning
confidence: 99%